A Frameshift Mutation in GRXCR2 Causes Recessively Inherited Hearing Loss. Issue 5 (7th April 2014) - Imtiaz, Ayesha; Kohrman, David C.; Naz, Sadaf
<x xml:space="preserve">Abstract</x> We mapped a new deafness locus DFNB101 and discovered an insertion mutation in GRXCR2 as the cause of moderate‐to‐severe hearing loss in humans. The frameshift mutation was predicted to affect the conserved, cysteine‐rich domain of GRXCR2, and to result in an abnormal extension of the C‐terminus. Cell transfection experiments demonstrated that the mutant protein is unstable and mislocalized relative to the wild type GRXCR2, consistent with a loss of function mutation. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>